A study of clinico-diagnostic profile and antibiogram in children with enteric fever in a tertiary care hospital - Jain, Bulbul; Mandot, Sanjay; Patel, Darshini (International Journal of Contemporary Pediatrics, 2022)
Background: Enteric fever remains a major concern in developing countries caused by Salmonella typhi. Recently, an upsurge in antimicrobial resistant strains has complicated the management. The present study was undertaken to evaluate the clinical profile, compare typhidot test with blood culture and determine antimicrobial susceptibility pattern. Methods: Single centre descriptive study was conducted by enrolling children who presented with fever and who were either blood culture positive for S. typhi or typhidot positive. The clinico-laboratory data and antibiogram was studied. Results: Out of 76 cases, blood culture was positive in 35 (46%) cases. Typhidot test showed 92.11% positivity. Abdominal pain (78%), vomiting (68%), hepatomegaly (68%) and splenomegaly (43%) were most commonly observed. The sensitivity for classical drugs chloramphenicol, ampicillin and cotrimoxazole was 88.57%, 74.28% and 77.14%. High susceptibility to ceftriaxone (97.14%) and high resistance to ciprofloxacin (55.14%) was observed. Conclusions: Prompt diagnosis of enteric fever is essential for appropriate management therefore, important to have conventional tests like typhidot test. There is re-emergence of sensitivity to the classical drugs. Ceftriaxone as monotherapy is quite effective. Effective vaccination strategy and hygienic practices can decrease the burden of this disease.